The influence of fish farm activity on the social structure of the common bottlenose dolphin in Sardinia (Italy) - Frau,Serena; Ronchetti,Fabio; Perretti,Francesco; Addis,Alberto; Ceccherelli,Giulia; La Manna,Gabriella (PeerJ, 2021)
In a wide variety of habitats, including some heavily urbanised areas, the adaptability of populations of common bottlenose dolphin (Tursiops truncatus) may depend on the social structure dynamics. Nonetheless, the way in which these adaptations take place is still poorly understood. In the present study we applied photo-identification techniques to investigate the social structure of the common bottlenose dolphin population inhabiting the Gulf of Alghero (Sardinia, Italy), analysing data recorded from 2008 to 2019. The social structure analysis showed a division of the entire population into five different communities and the presence of non-random associations, while there was no evidence of segregation between sexes. Furthermore, results highlighted an important change in social structure through time, likely due to a reduction in fish farm activity since 2015. The division of the population into different communities, the presence of segregation based on the foraging strategy (inside or outside the fish farm area) and the social network measures were evaluated by analysing independently the two datasets: the intense and low farm activity periods: 2008–2014 and 2015–2020, respectively. Segregation among individuals belonging to the same foraging strategy class was found only in the earlier period, and the composition of the four communities was consistent with this result. Our study improves the knowledge about bottlenose dolphin adaptation, as a lower complexity in social structure was linked to a reduction in anthropogenic food availability.
Keywords: Behavioural ecology; Human influence; Marine mammals; Fission fusion society; Foraging behaviour